Emotional labour under public management reform: an exploratory study of school teachers in England. Issue 19 (27th October 2016) - Rayner, Julie; Espinoza, Daniel E.
Abstract : This study uses the concept of emotional labour to illuminate areas of pressure and strain for teachers in English primary and secondary schools. It explores the impact of aspects of new public management reform on the nature and differences in the emotional labour experienced by teachers. The aim of this research was to help us understand the difficulties and tensions that this group of public sector professionals may be experiencing in the current environment. This research investigates the emotional side of teaching as a source of both job satisfaction and stress, in a performance-driven education sector. Findings show that the emotional labour presented differs in terms of its source, severity and impact on educational and personal goals and also that prescriptive and bureaucratically driven teaching frustrates teachers. The study contributes to the growing literature on emotional labour distinctive to public institutions. Theoretical and practical implications for recruitment, selection and training are discussed concluding with a research agenda.